(3GdOhQ GdbjGOj deOjQ GdeOQSI GdQSejI aj efWbI GdRgQGfj (B((3bVGA UjOG(B)s - (3WYeI, EHQGgje eMeOs ((3HjQhJs (3GdLGeYI GdGSdGejI (B- (3cdjI GdCOGH hGdYdhe GdGfSGfjIs, 2014)
(3JHjf gPg GdOQGSI CgejI OhQ GdeOjQ GdbGFO aj GdfghV HGdeOQSI hGdJUOj ddeTcdGJ GdJj JYJQVgG hHNGUI GdeOQSI GdQSejI GdJj JYGfj GdcKjQ ef GdeTcdGJ(B. (3hbO HjfJ GdOQGSI fbGW GdVYa ef fGMjI YOe Jecf eOjQj GdeOGQS GdQSejI ef dYH OhQ bjGOj GfWdGbkG ef YOe hLhO UdGMjGJ eYWGI dge, hZjGH EYOGOge GdeSHb, hcKQI GdCYHGA GdedbGI Ydi YGJbge(B. (3EP HjfJ GdOQGSI hLhO eOGQS QSejI HMGdI eRQjI LOkG ef fGMjI GdHfGA GdeOQSj hYOe UdGMg HCf jchf eOQSI(B. (3hGdCNWQ ef Pdc Cf eYdej heOjQj HYV gPg GdeOGQS dG jeJdchf GdMO GdCOfi ef ebheGJ GdYed GdJQHhj hGdYedjI GdJYdjejI GdJYqdejI, hgPG CeQ Sha jDOj aj fgGjI GdeWGa Edi aQR WHbGJ LGgdI aj GdeLJeY(B.s
(3GdfhY (B: (3QSGdIs
Keywords: (3GdGOGQI GdeOQSjIs; Gestion scolaire; Leadership; Leadership Zahrani; Public Sector; School management; Secteur Public; Zahrani; (3GdJYdje GdQSejs; (3GdbjGOI GdRgQGfjs